2013
DOI: 10.1208/s12249-013-9940-6
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Pseudopolymorphs of 10-Deacetyl Baccatin III

Abstract: Abstract. Three new solvates [mono-dimethyl sulfoxide (mono-DMSO), mono-dimethyl acetamide (mono-DMA) and mono-dimethyl formamide (mono-DMF)] of 10-Deacetyl baccatin III, were generated by slow evaporation in DMSO, DMF, and DMSO/DMA (1:1) solvent systems respectively. Two concomitant forms mono-DMSO(a new form) and di-DMSO (a known form) were obtained in the DMSO solvent system. Yet two other concomitant forms mono-DMA (a new form) and di-DMSO (a known form) were obtained in DMSO/DMA (1:1) solvent system. A fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Here, one unigene encoding DBAT and two unigenes encoding BAPT were identified, and they predominantly expressed in P. chienii . In pharmaceuticals industry, baccatin III and 10-DAB are key starting material of pacitaxel [ 46 ]. Our data showed that baccatin III and 10-DAB highly accumulated in P. chienii , suggesting a great economic value of P. chienii extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Here, one unigene encoding DBAT and two unigenes encoding BAPT were identified, and they predominantly expressed in P. chienii . In pharmaceuticals industry, baccatin III and 10-DAB are key starting material of pacitaxel [ 46 ]. Our data showed that baccatin III and 10-DAB highly accumulated in P. chienii , suggesting a great economic value of P. chienii extracts.…”
Section: Discussionmentioning
confidence: 99%